Echocardiographic Epicardial Adipose Tissue Thickness for Risk Stratification of Patients With Heart Failure - Parisi, Valentina; Conte, Maddalena; Petraglia, Laura; Grieco, Fabrizio Vincenzo; Bruzzese, Dario; Caruso, Aurelio; Grimaldi, Maria Gabriella; Campana, Pasquale; Gargiulo, Paola; Paolillo, Stefania; Attena, Emilio; Russo, Vincenzo; et al. (Frontiers in Physiology, 2020)
Background and aims. Epicardial adipose tissue (EAT) has been shown to be involved in the pathogenesis and progression of heart failure (HF). In this study we aimed to explore the predictive value of echocardiographic EAT thickness on prognosis of a selected population of HF patients. Methods. The patient population included n. 69 consecutive patients with systolic HF referred to implantable cardioverter defibrillator (ICD) implantation for primary or secondary prevention. At the time of enrolment, echocardiographic EAT thickness was assessed in all patients along with demographic and clinical data. The study had a median follow-up time of 49.8 months. We assessed the prognostic predictive value of EAT thickness on a composite clinical and arrhythmic outcome including HF related deaths, new hospital admissions for HF worsening, and atrial and life threatening ventricular arrhythmic events. Clinical and arrhythmic outcomes were also evaluated separately. Results. At univariate analysis, EAT thickness significantly predicted all the three outcomes considered. Of interest, at multivariate analysis, after adjusting for known risk factor, EAT remained significantly associated to the composite [HR 1.18 (1.09 to 1.28); p<0.001], arrhythmic [HR 1.14 (1.03 to 1.25); p=0.008], and clinical [HR 1.14 (1.03 to 1.27); p=0.010] outcomes. Conclusions. Echocardiographic assessment of EAT can predict outcome of HF patients and it is significantly associated with both arrhythmic and clinical events. These preliminary findings pave the way for future and larger studies aimed to definitively recognize the prognostic value of this novel risk marker in HF.